The Effect of Memo Intervention (Motivation, Enrichment, Mentoring and Operant Conditioning) on Nurses Caring Behavior - Memorya Yani Kharismawati; Tri Ismu Pujiyanto; Fery Agusman Motuho Mendrofa (GLOBAL HEALTH SCIENCE GROUP, 2026)
Caring is a core dimension of nursing practice, yet it varies significantly across regions and health systems. In Indonesia, approximately 35% of nurses exhibit poor caring behaviors, and Panti Wilasa dr. Cipto Hospital continues to receive complaints regarding the quality of nurse care. Objective to evaluate the effect of MEMO (Motivation, Enrichment, Mentoring, Operant Conditioning) intervention on nurses' caring behavior at Panti Wilasa dr Cipto Hospital Quasi-experimental quantitative study with One-Group Pretest-Posttest Design as many as 122 nurses with ≥ 8 years of service were selected through purposive sampling. MEMO intervention was implemented for three weeks. Caring behavior was evaluated before and after the intervention using valid observation instruments based on Swanson's Caring Theory. Data were analyzed by Wilcoxon Signed Rank Test due to non-normal distribution of data. Component effects were evaluated through ANOVA. Caring behavior scores significantly increased from a mean of 16.06 before the intervention to 18.14 after the intervention (p = 0.000). All MEMO components significantly influenced caring behavior: Motivation (F = 12.984, p = 0.000), Enrichmnet (F = 11.778, p = 0.001), Mentoring (F = 9.763, p = 0.002), and Operant Conditoning (F = 8.201, p = 0.005).MEMO intervention effectively and significantly improved nurses' caring behavior.